Dead Silent: Life Stories of Girls and Women Killed by the Italian Mafias, 1878-2018 - (:unkn) unknown (My University, 2019)
The first history of its kind in English, this work reconstructs the life stories of over two-hundred girls and women who lived throughout the regions of Italy from 1878 to 2018, and were killed by members of the Italian mafia organizations, which include the camorra, Cosa Nostra, ’ndrangheta, and the United Sacred Crown. Each life history seeks first of all to identify the victim with her own name, and draw out the uniqueness and individuality of her life and history, as documented by scattered traces left in interviews, diaries, testimonies, newspaper archives, and Italian antimafia web sites. As revealed by their histories, many of the victims had no ties to the mafia, and were caught unawares, killed while occupied in common pastimes of daily life, while others died as punishment for breaking unwritten criminal laws dominating the diverse communities where they lived. Several lives chronicled here provide insights on both women who fought for freedom from the mafias and the right to truth and justice, and female victims of vendettas committed to settle scores between mafia men. While creating a space for their life stories in cultural memory, the resultant history of Italy documents the mafias’ systemic use of murder against women and young girls since the very beginnings of the criminal organizations. The victims’ lives and premature, traumatic deaths thus stand as strong evidence refuting the myths that the mafia does not harm women or children, or that the so-called old mafia protected them. Hot links enable readers to access a rich array of additional resources.
Keywords: women and the mafia; femicide and the mafia; mafia victims; camorra; Cosa Nostra; ’ndrangheta; United Sacred Crown; Italian history